An investigation of athletes' anxiety of catching Covid-19 and their motivation levels in terms of some variables - Cevahircioglu, B.; Karakus, K. (African Educational Research Journal, 2021)
This study aims to examine the anxiety levels and motivation levels of athletes about catching covid-19 in terms of some variables. The sample group of the study consists of 204 women (51%) and 196 men (49%) in total, 400 athletes aged 18 and over, who are licensed in various branches. In the study, "Athletes' Anxiety of Catching New Type Coronavirus (Covid 19) Anxiety Scale (AAOCNTCAS)" developed by Tekkursun Demir et al. (2020) and "Sport-Specific Achievement Motivation Scale" (SSAMS) developed by Willis (1982) and adapted in Turkish by Tiryaki and Gödelek (1997) are utilized. The Skewness-Kurtosis test was used to determine whether the data showed a normal distribution. As a result, t-test and One-Way Anova tests were used to analyze the data. The Post Hoc Tukey test was used for multiple comparisons. As a result of the research, A statistically significant difference was found between the demographic characteristics of the athletes` anxiety about catching Covid-19 and their achievement motivation by, age, gender, education status, mother's education status, monthly income, athlete license category and total licensed sports year, while no statistically significant was found on paternal education status and type of sport. As a result of the findings, it is predicted that the anxiety levels of catching coronavirus may decrease by providing the necessary motivation to the athletes.